2022
DOI: 10.1088/1742-6596/2189/1/012016
|View full text |Cite
|
Sign up to set email alerts
|

Monthly-scale runoff forecast model based on PSO-SVR

Abstract: The current methods used in the Lubbog reservoir runoff forecast generally have shortcomings such as low forecast accuracy and low stability. Aiming at these problems, this paper constructs a PSO-SVR mid-and-long term forecast model, and it uses the particle swarm optimization algorithm (PSO) to find the penalty coefficient C, the insensitivity coefficient ε and the gamma parameter of the Gaussian radial basis kernel function of the support vector regression machine (SVR). The results demonstrates that the ave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…In this study, a Dropout layer is set in the LSTM model to reduce the model's excessive dependence on training data and decrease the risk of model overfitting. Related studies [29][30][31] have shown that utilizing heuristic optimization algorithms to optimize the parameters of the LSTM model can effectively improve their accuracy in runoff prediction. The particle swarm optimization (PSO) is a population intelligence optimization algorithm inspired by the study of bird flocking behavior.…”
Section: Apso-lstm Modelmentioning
confidence: 99%
“…In this study, a Dropout layer is set in the LSTM model to reduce the model's excessive dependence on training data and decrease the risk of model overfitting. Related studies [29][30][31] have shown that utilizing heuristic optimization algorithms to optimize the parameters of the LSTM model can effectively improve their accuracy in runoff prediction. The particle swarm optimization (PSO) is a population intelligence optimization algorithm inspired by the study of bird flocking behavior.…”
Section: Apso-lstm Modelmentioning
confidence: 99%
“…In the past, hydrological models were generally used, but these models required a lot of parameters, such as temperature, soil moisture, soil type, slope, terrain, etc., and different parameters also contained very complex relationships [3]. In recent years, machine learning technology has developed rapidly, and many researchers have found that its efficient data parallel processing ability can be applied to the field of flood prediction [4,5].…”
Section: Introductionmentioning
confidence: 99%